The BRCT domains of ECT2 have distinct functions during cytokinesis - Schneid, Sandra; Wolff, Friederike; Buchner, Kristina; Bertram, Nils; Bayguen, Seren; Barbosa, Pedro; Mangal, Sriyash; Zanin, Esther (Cell Reports, 2021)
During cell division, the guanine nucleotide exchange factor (GEF) ECT2 activates RhoA in a narrow zone at the cell equator in anaphase. ECT2 consists of three BRCT domains (BRCT0, 1, and 2), a catalytic GEF, and a pleckstrin homology (PH) domain. How the conserved BRCT domains spatially and temporally control ECT2 activity remains unclear. We reveal that each BRCT domain makes distinct contributions to the ECT2 function. We find that BRCT0 contributes to, and BRCT1 is essential for, ECT2 activation in anaphase. BRCT2 integrates two functions: GEF inhibition and RACGAP1 binding, which together limit ECT2 activity to a narrow zone at the cell equator. BRCT2-dependent control of active RhoA zone dimension functions in addition to the inhibitory signal of the astral microtubules. Our analysis provides detailed mechanistic insights into how ECT2 activity is regulated and how that regulation ensures, together with other signaling pathways, successful cell division. Schneid et al. show that the three BRCT domains of ECT2 make distinct contributions to RhoA zone formation and cytokinesis. BRCT0 and BRCT1 bind RACGAP1 and promote ECT2 activation. In contrast, BRCT2 inhibits GEF activity and BRCT2 binding to RACGAP1 limits ECT2 activity spatially to the cell equator.
CRIS-Team Scopus Importer:2021-05-26
Keywords: BRCT domain; cell division; Cyk4; cytokinesis; ECT2; PLK1; RACGAP1; RhoA